2019
DOI: 10.12965/jer.1938116.058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of winter skiing on stress, heart rate, apprehension, and enjoyment in collegiate students: a single randomized controlled trial

Abstract: This study investigated the effect of winter skiing on stress levels in collegiate students and also observed psychological factors related to heart rate, apprehension, and enjoyment. Two hundred thirty-eight male students were randomly classified into the control group (n= 117) or the ski group (n= 121). The control group received lectures on skiing; however, the ski group received practical ski training. Psychological measures included stress, apprehension, and enjoyment; physical measures included heart rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The practical exercise or activity in PE is a kind of active learning in which students learn by 'doing' [35,36]. Austin and Mescia [37] suggested that through this process students engage in higher-order thinking, including analysis, synthesis, and evaluation, and this allows them to assimilate, apply and, retain newly acquired information.…”
Section: Discussionmentioning
confidence: 99%
“…The practical exercise or activity in PE is a kind of active learning in which students learn by 'doing' [35,36]. Austin and Mescia [37] suggested that through this process students engage in higher-order thinking, including analysis, synthesis, and evaluation, and this allows them to assimilate, apply and, retain newly acquired information.…”
Section: Discussionmentioning
confidence: 99%
“…One of the ways to "reset" somatic and psychological processes from the effects of occupational stress may be to have a break, for example by taking a holiday. Not surprisingly, the limited body of research on health effects of holidays reports significant positive health effects and a reduction in stress [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the researcher surmised that students' mitigated enthusiasm, learning, and appreciation for traditional games could be due to the lack of nonverbal and contextual clues, human touch, and engagement inherent in online teaching (Nguyen & Dolan, 2022). Moreover, the absence of "doing" in games may have hampered students' enjoyment and learning since doing practical exercises helps students learn better (Lee et al, 2019;Park et al, 2017). Traditional Filipino games, like any other traditional game, are a form of cultural expression representing the values of the communities in which they are played (Lavega-Burgués & Navarro-Adelantado, 2019).…”
Section: Discussionmentioning
confidence: 99%